Reexamining the Abraham Accords: The Dynamics of the Abraham Alliance Amid Geopolitical Uncertainly - Pambagyo, Wahyu Dwi; Maksum, Ali (Journal Of Middle East and Islamic Studies, 2025)
Several studies have discussed the bilateral economic impact of the Abraham Accords, but few of them have thoroughly examined how this agreement has evolved into a collective security framework amid global geopolitical changes. This study attempts to fill the existing research gap by analyzing the transformation of the Abraham Accords into the Abraham Alliance using the Balance of Power theory framework developed by Stephan M. Walt. Using a qualitative approach and case study mode, this study examines secondary data from 2020 to 2025, using academic journals, government policy documents, and reliable news media as sources. This study concludes that the alliance is more influenced by the need to balance the perceived threat from Iran, rather than solely based on economic interests. Since the conflict between Palestine and Israel erupted on October 7, 2023, the countries that signed the agreement have continued to prioritize strategic security and maintain relations with Israel. The possibility of Saudi Arabia and Syria joining the alliance indicates a new direction toward more pragmatic and security-focused regional security. With this research, it is hoped that theoretically, by developing this framework, the Abraham Alliance can be understood as a new category in analyzing the region.